Different influence of cooperation and public funding on innovation activities within German industries - Prokop, Viktor; Stejskal, Jan (Journal of Business Economics and Management, 2019)
The aim of this research is to analyse (i) influence of cooperation with different partners and public funding on firms´ willingness to innovate; (ii) how public funding and cooperation with different partners influence firms´ innovation performance (turnover); (iii) effects of mutual interactions between firms´ innovation activities, cooperation with different partners and public funding on firms´ innovation performance (measured with turnover). The situation of 561 firms in Machines and Equipment industries in Germany was analysed because it is one of the most competitive economy in the world and one of the leaders in innovation within European Union. It allows to create unique benchmark and to propose implications that will be more appropriate and applicable also in other countries. For analyses, the data from Community Innovation Survey 2012-2014, which is a harmonized questionnaire and provides EU's science and technology statistics, was used, and new binary and multiple linear regression models were employed. Results of analyses show that provision of public subsidies, unlike cooperation, strongly influence firm’s motivation to innovate. However, results also showed that supported innovation activities do not always lead to an increase in firms´ innovative performance. Therefore, it can be pointed to the phenomenon of inefficiency of public innovation support in final consequence.